EFEKTIVITAS PROGRAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA (P4MI) DALAM MENANGANI PRAKTIK EKSPLOITASI JARINGAN PENEMPATAN ILEGAL - Mohamad Razif Panigoro; Lisnawaty W. badu; Waode Mustika (Universitas Harapan Medan, 2026)
This study aims to analyze the effectiveness of the Indonesian Migrant Worker Protection Program (P4MI) in handling exploitation practices through illegal placement networks, with a case study at P4MI Gorontalo for the 2024–2025 period. The research method employs an empirical juridical approach with descriptive-analytical specifications. Data were collected through documentation studies and in-depth interviews, then analyzed qualitatively. The results show that P4MI Gorontalo is moderately effective in its preventive function, evidenced by successfully preventing 5 prospective migrant workers from going to Cambodia and repatriating 2 victims of human trafficking. However, its effectiveness is low in the repressive function because P4MI lacks law enforcement authority, resulting in no illegal network perpetrators being prosecuted. Inhibiting factors include limited personnel and infrastructure, low public legal literacy, and overlapping regulations. The conclusion is that P4MI has not been optimal in providing comprehensive legal protection. Regulatory harmonization, strengthening P4MI's authority, and enhancing bilateral cooperation with destination countries are required.